A method for preparing high-temperature resistant, lightweight and high-strength thermal insulation tile

By using silicon sol, silicon powder and polymer organic materials for ball milling and spraying in the preparation process of thermal insulation tile, and combining with the precipitation and sintering process of boron nitride powder, the problems of uneven strength and insufficient temperature resistance of thermal insulation tile are solved, and high-strength and high-temperature insulation tile preparation is achieved.

CN117069501BActive Publication Date: 2025-04-29AEROSPACE INST OF ADVANCED MATERIALS & PROCESSING TECH
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202310869191.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-07-14
Publication Date
2025-04-29
Estimated Expiration
2043-07-14

AI Technical Summary

Technical Problem

During the preparation process, existing heat insulation tiles have problems such as uneven distribution of sintering additives and differences in ceramic fiber density, resulting in uneven strength and insufficient temperature resistance.

Method used

Silicon sol and silicon powder ball mill were mixed with silicon powder, sprayed on the surface of ceramic fibers, and ball milling was combined with polymer organic matter and boron nitride powder and precipitated in water. The insulation tiles were prepared by reduced pressure distillation concentration and step-by-step heating sintering.

Benefits of technology

The insulation tiles maintain good structural strength and temperature resistance at high temperatures, have low density and high compression strength, and can maintain stable performance in a wide temperature range of 600 to 1500°C.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117069501B_ABST
    Figure CN117069501B_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing a high-temperature resistant, lightweight, high-strength thermal insulation tile, and belongs to the technical field of thermal protection materials. In this method, a composition A is obtained from silica sol and silicon powder, and is evenly sprayed on the surface of a high-temperature resistant short-cut ceramic fiber M, and then evenly sprayed with a polymer organic solution after in-situ drying, and a modified short-cut ceramic fiber M is obtained after in-situ drying; a mixture B is obtained from boron nitride powder and a polymer organic solution, and a modified flocculent solid mixture B is obtained after treatment; quartz fiber, modified short-cut ceramic fiber M, modified flocculent solid mixture B, and an adhesive additive C are mixed into a slurry D, which is concentrated by vacuum distillation, poured into a filter mold to filter out moisture, and then the wet blank is taken out, and it is clamped with a form-fitting tool and dried to obtain a dry blank E; the dry blank E is transferred to an air muffle furnace for step-by-step temperature sintering and cooling to obtain a high-temperature resistant, lightweight, high-strength thermal insulation tile.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of heat protection materials, and specifically relates to a method for preparing a high-temperature resistant, lightweight and high-strength heat-insulating tile. Background Art

[0002] As a traditional thermal insulation material, rigid thermal insulation tiles have significant advantages over aerogels, thermal insulation felts and other thermal insulation materials, such as high strength, good erosion resistance and reusability. They are one of the important thermal protection materials for space shuttles. However, due to some unresolved problems in the preparation process of thermal insulation tiles, the high temperature resistance and mechanical strength of thermal insulation tiles have not yet reached the ideal level. The main problems include: sintering aids such as boron nitride, boron carbide, and silica sol are added to the thermal insulation tiles in the form of powder or liquid directly in the slurry. Affected by the density difference, it is very easy to cause the residual amount of sintering aids to be uncontrollable during the filtration and drying process, which not only leads to uneven gradient distribution in the thickness direction, but also during the drying process of the wet blank, affected by the evaporation and migration of the liquid during drying, the sintering aid powder inside the thermal insulation tile will migrate to the surface of the thermal insulation tile with the evaporation of the liquid, resulting in uneven strength of the thermal insulation tile. In addition, for thermal insulation tiles made of two types of ceramic fibers, due to the density difference between the fibers, the two types of fibers have different sedimentation rates during the filtration process, which further leads to uneven distribution of fibers in the thermal insulation tiles, thus affecting the strength and temperature resistance of the thermal insulation tiles. For thermal insulation tiles made of two types of ceramic fibers, since there is only one sintering aid and the two types of ceramic fibers are sintered as one, there is a difference in thermal expansion coefficients between the fibers. When the formed thermal insulation tiles are heated, the thermal expansion coefficients between the fibers do not match, and one of the fibers shrinks or expands too much at high temperature, resulting in a decrease in the mechanical properties of the thermal insulation tiles. In order to solve the above problems, it is necessary to further study the preparation methods of high-temperature resistant, high-strength and lightweight thermal insulation tiles. Summary of the invention

[0003] The purpose of the present invention is to provide a method for preparing a high-temperature resistant, lightweight and high-strength thermal insulation tile to overcome the above-mentioned technical problems.

[0004] To achieve the above object, the present invention adopts the following technical solutions:

[0005] A method for preparing a high-temperature resistant, lightweight, high-strength thermal insulation tile comprises the following steps:

[0006] 1) ball-milling the silica sol and the silicon powder in a closed environment to obtain a composition A;

[0007] 2) spraying the composition A uniformly on the surface of the high temperature resistant short chopped ceramic fiber M, drying it in situ, and then spraying the polymer organic solution uniformly on the surface of the high temperature resistant short chopped ceramic fiber M, drying it in situ, to obtain the modified short chopped ceramic fiber M;

[0008] 3) mixing the boron nitride powder and the polymer organic solution by ball milling to obtain a mixture B, pouring the mixture B into rapidly rotating dispersed water to precipitate the solid matter in the mixture B in the water, filtering and drying to obtain a flocculent solid mixture B; further subjecting the flocculent solid mixture B to a hydrophilic treatment to obtain a modified flocculent solid mixture B;

[0009] 4) adding quartz fiber, modified short-cut ceramic fiber M, modified flocculent solid mixture B, and bonding agent C into water in a certain proportion and uniformly dispersing them to obtain slurry D;

[0010] 5) Under stirring, the slurry D obtained in step 4) is concentrated by vacuum distillation until the amount of water added is several times the total mass of the quartz fiber and the modified chopped ceramic fiber M, thereby obtaining a concentrated slurry D;

[0011] 6) Pour the concentrated slurry D obtained in step 5) into a filtering mold to filter out water, take out the wet blank, clamp it with a form-fitting tool and dry it to obtain a dry blank E;

[0012] 7) The dry blank E obtained in step 6) is transferred to an air muffle furnace for step-by-step temperature sintering. After sintering, the heating is turned off and the blank is taken out after cooling to room temperature to obtain a high-temperature resistant, lightweight and high-strength thermal insulation tile.

[0013] Furthermore, in step 1), the mass ratio of the silica sol to the silicon powder is (2-5):1.

[0014] Furthermore, in step 2), the mass ratio of the composition A to the high temperature resistant chopped ceramic fibers M is (0.1-5):100.

[0015] Furthermore, the high temperature resistant chopped ceramic fiber M in step 2) has better heat resistance than quartz fiber, and is preferably one of alumina fiber, zirconia fiber and mullite fiber.

[0016] Furthermore, the high temperature resistant chopped ceramic fibers M in step 2) have a length ranging from 1 to 15 mm and a diameter ranging from 0.5 to 10 μm.

[0017] Furthermore, in step 2), the mass ratio of the high molecular organic matter to the high temperature resistant chopped ceramic fibers M is (0.1-1):100.

[0018] Furthermore, in step 3), the mass ratio of the boron nitride powder to the polymer organic solution is not greater than 1:1.5, and the boron nitride powder should be completely infiltrated in the polymer organic solution.

[0019] Furthermore, the conditions that the high molecular organic matter in steps 2) and 3) should meet are: insoluble in water, and the element composition includes C, H, and O.

[0020] Furthermore, in step 3), the volume of the water is at least 5 times the volume of the mixture B.

[0021] Furthermore, the speed of the rapid rotation dispersion in step 3) is at least 3000 r / min.

[0022] Furthermore, the quartz fiber in steps 4) and 5) has a length ranging from 1 to 15 mm and a diameter ranging from 0.5 to 10 μm.

[0023] Furthermore, the quartz fiber and the modified chopped ceramic fiber M in step 4) can be mixed in any mass ratio, preferably in the mass ratio range of (1 to 100):10.

[0024] Furthermore, in step 4), the amount of the modified flocculent solid mixture B added is: the content of boron nitride in the modified flocculent solid mixture B accounts for (0.1-5):100 of the total mass of the quartz fiber and the modified chopped ceramic fiber M.

[0025] Furthermore, the bonding aid C in step 4) is one of starch and polyvinyl alcohol, and the added amount is 0.5‰ to 2‰ of the water mass.

[0026] Furthermore, the amount of water added in step 4) is 50 to 500 times the total mass of the quartz fiber and the modified chopped ceramic fiber M.

[0027] Furthermore, in step 5), the amount of water added is 5 to 10 times the total mass of the quartz fiber and the modified chopped ceramic fiber M.

[0028] Furthermore, the conformable tooling in step 6) is used to control the clamping compression amount of the wet blank to achieve a density of the dry blank E between 0.1 and 0.5 g / cm 3 Quantitative control within the range.

[0029] Furthermore, the stepwise temperature rise sintering in step 7) is as follows: firstly, the temperature is raised to 500-600°C and kept for 1-3 hours, then the temperature is raised to 800-900°C and kept for 1-3 hours, and finally the temperature is raised to 1100-1200°C and kept for 1-2 hours.

[0030] The beneficial effects achieved by the present invention are as follows:

[0031] 1. The prepared high-temperature resistant, lightweight, high-strength thermal insulation tile can generate a borosilicate glass phase with a temperature resistance of 1200°C at the quartz fiber overlap point through boron nitride, thereby realizing high-strength sintering connection of the quartz fiber; by generating a silicon dioxide phase with a temperature resistance of more than 1500°C at high temperature through silica sol and silicon powder, the sintering connection of the overlap points of the ceramic fibers M can be realized; the two types of fibers each generate an overlap network structure, which is interlaced with each other, achieving the coordination of the thermal expansion coefficient while ensuring that the thermal insulation tile has good structural strength in the entire wide temperature range of 600-1500°C; at 0.3g / cm 3 At a density of , the room temperature compression strength can reach more than 1.5MPa;

[0032] 2. Through step 2), high-strength sintering and uniform distribution of the chopped ceramic fibers M can be achieved, thereby improving the temperature resistance of the thermal insulation tile, and the long-term temperature resistance can reach above 1500°C. First, through step 2), uniform and firm sintering reaction sites can be provided on the surface of the chopped ceramic fibers M; secondly, the organic matter can reduce the density of the chopped ceramic fibers M, making the density of the chopped ceramic fibers M close to that of the quartz fibers, thereby avoiding the difference in sedimentation velocity caused by the different densities of the two fibers, and ultimately leading to uneven fiber distribution of the product.

[0033] 3. Through step 3), the content of boron nitride in the thermal insulation tile can be controlled and evenly distributed, thereby ensuring that the strength of the thermal insulation tile is controllable. First, this method can prevent the boron nitride powder from being lost in large quantities and uncontrollably when filtering out water in the filtration mold; in addition, through this treatment method, the dispersion state of the boron nitride powder in water can be reduced, avoiding the uneven distribution of boron nitride in the thermal insulation tile body due to poor wettability of boron nitride with water, excessive density of boron nitride, and rapid sedimentation.

[0034] 4. Through step 5), the anisotropy of the fibers in the slurry can be retained to the maximum extent, avoiding the oriented distribution of the fibers in the plane caused by direct filtration, and further causing the strength loss in the thickness direction. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 The present invention is a flow chart of a method for preparing a high-temperature resistant, lightweight and high-strength thermal insulation tile. DETAILED DESCRIPTION

[0036] In order to make the various technical features and advantages or technical effects in the above technical solutions of the present invention more obvious and easy to understand, they are described in detail below with reference to the accompanying drawings.

[0037] Example 1

[0038] 1) mixing silica sol and silicon powder by ball milling in a closed environment at a mass ratio of 2:1 to obtain a composition A;

[0039] 2) The composition A is uniformly sprayed on the surface of alumina fiber (fiber length is 1 to 15 mm, fiber diameter is 0.5 to 10 μm), the mass ratio of the composition A to the alumina fiber is 0.1:100, and after in-situ drying, the ethyl acetate solution of polyvinyl butyral is continued to be uniformly sprayed on the surface of the alumina fiber. After in-situ drying, modified alumina fiber is obtained; the mass ratio of polyvinyl butyral to alumina fiber is 0.1:100.

[0040] 3) mixing boron nitride powder and polyvinyl butyral solution by ball milling, with the mass ratio of boron nitride powder to polyvinyl butyral solution being 1:2, to obtain a mixture B, pouring the mixture B into water that is 5 times the volume of the mixture and is rapidly rotated and dispersed at a speed of 3000 r / min, so that solid matter in the mixture B is precipitated in the water, filtered and then dried to obtain a flocculent solid mixture B; further subjecting the flocculent solid mixture B to a hydrophilic treatment to obtain a modified flocculent solid mixture B;

[0041] 4) Quartz fiber (fiber length is 1 to 15 mm, fiber diameter is 0.5 to 10 μm), modified alumina fiber, modified flocculent solid mixture B, and starch are added to water in a certain proportion and uniformly dispersed to obtain slurry D; wherein the mass ratio of quartz fiber to modified alumina fiber is 1:10, the content of boron nitride in the modified flocculent solid mixture B accounts for 0.5:100 of the total mass of quartz fiber and modified alumina fiber, the amount of starch added is 0.5‰ of the mass of water, and the amount of water added is 50 times the total mass of quartz fiber and modified alumina fiber.

[0042] 5) Under stirring, the slurry D obtained in step 4) is concentrated by vacuum distillation until the amount of water added is 5 times the total mass of the quartz fiber and the modified alumina fiber, thereby obtaining a concentrated slurry D;

[0043] 6) Pour the concentrated slurry D obtained in step 5) into a filtering mold to filter out the water, take out the wet blank, clamp it with a form-fitting tool and dry it to obtain a dry blank E; the form-fitting tool is used to control the clamping compression amount of the wet blank to achieve a density of 0.5 g / cm 3 .

[0044] 7) The dry blank E obtained in step 6) is transferred to an air muffle furnace, kept at 500°C for 3 hours, then raised to 800°C for 3 hours, then raised to 1100°C for 2 hours, turned off the heating, cooled to room temperature and taken out to obtain a high-temperature resistant, lightweight and high-strength thermal insulation tile.

[0045] After testing, the prepared high-temperature resistant, lightweight, high-strength thermal insulation tile has a density of 0.5g / cm 3, room temperature compressive strength is 3.2MPa; the compressive strength fluctuation of different areas of the blank is less than 3%; after high-temperature treatment at 1500℃ in a muffle furnace for 30 minutes, the linear shrinkage rate is less than 1%.

[0046] Example 2

[0047] 1) ball-milling silica sol and silica powder in a mass ratio of 5:1 in a closed environment to obtain a composition A;

[0048] 2) The composition A is uniformly sprayed on the surface of alumina fiber (fiber length is 1 to 15 mm, fiber diameter is 0.5 to 10 μm), the mass ratio of the composition A to the alumina fiber is 5:100, after in-situ drying, the ethyl acetate solution of polyvinyl butyral is continued to be uniformly sprayed on the surface of the alumina fiber, after in-situ drying, modified alumina fiber is obtained; the mass ratio of polyvinyl butyral to alumina fiber is 1:100.

[0049] 3) mixing boron nitride powder and polyvinyl butyral solution by ball milling, with the mass ratio of boron nitride powder to polyvinyl butyral solution being 1:1.5, to obtain a mixture B, pouring the mixture B into rapidly rotating dispersed water having a volume 10 times that of the mixture B, so that solid matter in the mixture B is precipitated in the water, filtering and drying to obtain a flocculent solid mixture B; further subjecting the flocculent solid mixture B to a hydrophilic treatment to obtain a modified flocculent solid mixture B;

[0050] 4) adding quartz fiber (fiber length of 1 to 15 mm, fiber diameter of 0.5 to 10 μm), modified alumina fiber, modified flocculent solid mixture B, and polyvinyl alcohol into water in a certain proportion and uniformly dispersing them to obtain slurry D; wherein the mass ratio of quartz fiber to modified alumina fiber is 100:10, the content of boron nitride in the modified flocculent solid mixture B accounts for 5:100 of the total mass of quartz fiber and modified alumina fiber, the amount of polyvinyl alcohol added is 2‰ of the mass of water, and the amount of water added is 500 times the total mass of quartz fiber and modified alumina fiber.

[0051] 5) Under stirring, the slurry D obtained in step 4) is concentrated by vacuum distillation until the amount of water added is 10 times the total mass of the quartz fiber and the modified alumina fiber, to obtain a concentrated slurry D;

[0052] 6) Pour the concentrated slurry D obtained in step 5) into a filtering mold to filter out the water, take out the wet blank, clamp it with a form-fitting tool and dry it to obtain a dry blank E; the form-fitting tool is used to control the clamping compression amount of the wet blank to achieve a density of 0.1 g / cm 3 control.

[0053] 7) The dry blank E obtained in step 6) is transferred to an air muffle furnace, kept at 600°C for 1 hour, then raised to 900°C for 1 hour, then raised to 1200°C for 1 hour, turned off the heating, cooled to room temperature and taken out to obtain a high-temperature resistant, lightweight and high-strength thermal insulation tile.

[0054] After testing, the prepared high-temperature resistant, lightweight, high-strength thermal insulation tile has a density of 0.1g / cm 3 , room temperature compression strength is 0.5MPa; compression strength fluctuation is less than 5%; after high temperature treatment at 1500℃ in a muffle furnace for 30 minutes, the linear shrinkage is less than 3%.

[0055] Example 3

[0056] 1) mixing silica sol and silicon powder by ball milling in a closed environment at a mass ratio of 3:1 to obtain a composition A;

[0057] 2) spraying composition A uniformly on the surface of mullite fiber (fiber length of 1 to 15 mm, fiber diameter of 0.5 to 10 μm), the mass ratio of composition A to mullite fiber is 2:100, after in-situ drying, continue to uniformly spray ethyl acetate solution of polyvinyl butyral on the surface of mullite fiber, after in-situ drying, to obtain modified mullite fiber; the mass ratio of polyvinyl butyral to mullite fiber is 0.5:100;

[0058] 3) mixing boron nitride powder and polyvinyl butyral solution by ball milling, with the mass ratio of boron nitride powder to polyvinyl butyral solution being 1:3, to obtain a mixture B, pouring the mixture B into rapidly rotating dispersed water having a volume 10 times that of the mixture B, so that solid matter in the mixture B is precipitated in the water, filtering and drying to obtain a flocculent solid mixture B; further subjecting the flocculent solid mixture B to a hydrophilic treatment to obtain a modified flocculent solid mixture B;

[0059] 4) adding quartz fiber (fiber length of 1 to 15 mm, fiber diameter of 0.5 to 10 μm), modified mullite fiber, modified flocculent solid mixture B, and starch into water in a certain proportion and uniformly dispersing them to obtain slurry D; wherein the mass ratio of quartz fiber to modified mullite fiber is 50:10, the content of boron nitride in the modified flocculent solid mixture B accounts for 3:100 of the total mass of quartz fiber and modified mullite fiber, the amount of starch added is 1.5‰ of the mass of water, and the amount of water added is 200 times the total mass of quartz fiber and modified mullite fiber.

[0060] 5) Under stirring, the slurry D obtained in step 4) is concentrated by vacuum distillation until the amount of water added is 7 times the total mass of the quartz fiber and the modified mullite fiber, to obtain a concentrated slurry D;

[0061] 6) Pour the concentrated slurry D obtained in step 5) into a filtering mold to filter out the water, take out the wet blank, clamp it with a form-fitting tool and dry it to obtain a dry blank E; the form-fitting tool is used to control the clamping compression amount of the wet blank to achieve a density of 0.3g / cm 3 Quantitative control.

[0062] 7) The dry blank E obtained in step 6) is transferred to an air muffle furnace, kept at 600°C for 2 hours, then raised to 900°C for 2 hours, then raised to 1200°C for 1.5 hours, turned off the heating, cooled to room temperature and taken out to obtain a high-temperature resistant, lightweight and high-strength thermal insulation tile.

[0063] After testing, the prepared high-temperature resistant, lightweight, high-strength thermal insulation tile has a density of 0.3g / cm 3 , room temperature compressive strength is 1.8MPa; compressive strength fluctuation is less than 3%; after high temperature treatment at 1500℃ in a muffle furnace for 30 minutes, the linear shrinkage is less than 2%.

[0064] Comparative Example 1

[0065] The same amount of quartz fiber, mullite fiber, boron nitride powder and starch as in Example 3 were weighed and added to the same amount of water as in step 4) for uniform dispersion. After dispersion, the mixture was introduced into the filtration mold in step 6) of Example 3 to filter out the water, and the wet blank was taken out and clamped with the form-fitting tool in step 6) of Example 3 for drying. The density was 0.3 g / cm 3 The dry blank is quantitatively controlled. Then, the sintering process is the same as step 7 of Example 3, and the dry blank is transferred to an air muffle furnace, kept at 600°C for 2 hours, then raised to 900°C for 2 hours, and then raised to 1200°C for 1.5 hours, and then the heating is turned off, and the blank is taken out after cooling to room temperature to obtain a thermal insulation tile prepared by the conventional method.

[0066] After testing, the density of the conventional thermal insulation tile is 0.3g / cm 3 , room temperature compression strength is 0.95MPa; compression strength fluctuation is 10%; after high temperature treatment at 1500℃ in a muffle furnace for 30 minutes, the linear shrinkage rate is greater than 15%.

[0067] Although the present invention has been disclosed as above by way of embodiments, it is not intended to limit the present invention. Appropriate modifications or equivalent substitutions of the technical solutions of the present invention made by ordinary technicians in the field should all be included in the protection scope of the present invention. The protection scope of the present invention shall be based on what is defined in the claims.

Claims

1. A method for preparing a high-temperature resistant, lightweight, high-strength thermal insulation tile, characterized in that: The following steps are involved: 1) ball-milling the silica sol and the silica powder in a closed environment to obtain a composition A; 2) spraying the composition A uniformly on the surface of the high temperature resistant short chopped ceramic fiber M, drying it in situ, and then spraying the polymer organic solution uniformly on the surface of the high temperature resistant short chopped ceramic fiber M, drying it in situ, to obtain the modified short chopped ceramic fiber M; 3) The boron nitride powder and the polymer organic solution are mixed by ball milling to obtain a mixture B, the mixture B is poured into rapidly rotating dispersed water to precipitate the solid matter in the mixture B in the water, filtered and dried to obtain a flocculent solid mixture B; then the flocculent solid mixture B is subjected to a hydrophilic treatment to obtain a modified flocculent solid mixture B; 4) adding quartz fiber, modified chopped ceramic fiber M, modified flocculent solid mixture B, and bonding agent C into water in a certain proportion, and uniformly dispersing them to obtain slurry D; 5) Under stirring, the slurry D obtained in step 4) is concentrated by vacuum distillation until the amount of water added is 5 to 10 times the total mass of the quartz fiber and the modified chopped ceramic fiber M, thereby obtaining a concentrated slurry D; 6) Pour the concentrated slurry D obtained in step 5) into a filtering mold to filter out water, take out the wet blank, clamp it with a form-fitting tool and dry it to obtain a dry blank E; 7) The dry blank E obtained in step 6) is transferred to an air muffle furnace for stepwise temperature sintering. After sintering, the heating is turned off, and the blank is taken out after cooling to room temperature to obtain a high-temperature resistant, lightweight, and high-strength thermal insulation tile; The mass ratio of the composition A to the high temperature resistant chopped ceramic fiber M in step 2) is (0.1~5):100; the mass ratio of the high molecular organic matter to the high temperature resistant chopped ceramic fiber M is (0.1~1):100; the mass ratio of the boron nitride powder to the high molecular organic solution in step 3) is not greater than 1:1.5, and the boron nitride powder should be completely infiltrated in the high molecular organic solution.

2. The preparation method according to claim 1, characterized in that The mass ratio of the silica sol to the silica powder in step 1) is (2-5):

1.

3. The preparation method according to claim 1, characterized in that: The high temperature resistant chopped ceramic fiber M in step 2) is one of alumina fiber, zirconia fiber and mullite fiber, with a fiber length of 1-15 mm and a fiber diameter of 0.5-10 μm; and / or The conditions that the high molecular organic matter in steps 2) and 3) should meet are: insoluble in water, and the element composition includes C, H, and O.

4. The preparation method according to claim 1, characterized in that: In step 3), the volume of water is at least 5 times the volume of mixture B; and the speed of the rapid rotation dispersion is at least 3000 r / min.

5. The preparation method according to claim 1, characterized in that: In step 4), the mass ratio of the quartz fiber to the modified short-cut ceramic fiber M is (1-100):10; the amount of the modified flocculent solid mixture B added is: the content of boron nitride in the modified flocculent solid mixture B accounts for (0.1-5):100 of the total mass of the quartz fiber and the modified short-cut ceramic fiber M; the amount of water added is 50-500 times the total mass of the quartz fiber and the modified short-cut ceramic fiber M.

6. The preparation method according to claim 1 or 5, characterized in that: The quartz fiber in steps 4) and 5) has a fiber length of 1-15 mm and a fiber diameter of 0.5-10 μm.

7. The preparation method according to claim 1, characterized in that: The bonding aid C in step 4) is one of starch and polyvinyl alcohol, and the added amount is 0.5‰~2‰ of the water mass.

8. The preparation method according to claim 1, characterized in that: The following tooling in step 6) is used to control the clamping compression of the wet blank to achieve a density of the dry blank E between 0.1 and 0.5 g / cm 3 Quantitative control within the range.

9. The preparation method according to claim 1, characterized in that: The step-by-step sintering in step 7) is as follows: first, the temperature is raised to 500-600°C and kept for 1-3 hours, then the temperature is raised to 800-900°C and kept for 1-3 hours, and finally the temperature is raised to 1100-1200°C and kept for 1-2 hours.

Citation Information

Patent Citations

  • Preparation method of three-phase ceramic fiber composite heat insulation tile

    CN112125649A